Scenarios for technology transfer between university and industry. (LACCEI, 2024)
Abstract – From the constant challenges that the different economic sectors in society propose at a competitive and innovative level, and from the constant work of generating knowledge that is developed in universities, it is expected that the use of advanced research results can be seen as alternatives that mitigate the needs of the industry and therefore contribute to the strengthening of the market in the different economic contexts, reaching an impact on social, environmental and political phenomena of innovation ecosystems. However, in the face of technological development initiatives in the territories, it has been found that the articulation between the university and the industry has been limited by different factors, among which is the absence of information related to opportunities for the maturation of technologies, or including use and exploitation of these. However, a possible solution is found in the structuring of technology transfer strategies that the networks of actors can promote in their ecosystems, including in turn the intermediaries or facilitators of innovation, recognized as possible links that allow strengthening the networks of innovation in different situations that seek to generate cooperation, alliance or collaboration agreements between the university and industry. In this sense, the search for information related to possible models of articulation and generation of technology transfer scenarios has been carried out, where the inclusion of the inventors of the university and the technological recipients of the industry are highlighted. For this work, the Scopus database has been used, and a set of scenarios have been proposed that relate the topics under study.